If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(x + 3) = -2(2x + 6) Reorder the terms: 11(3 + x) = -2(2x + 6) (3 * 11 + x * 11) = -2(2x + 6) (33 + 11x) = -2(2x + 6) Reorder the terms: 33 + 11x = -2(6 + 2x) 33 + 11x = (6 * -2 + 2x * -2) 33 + 11x = (-12 + -4x) Solving 33 + 11x = -12 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 33 + 11x + 4x = -12 + -4x + 4x Combine like terms: 11x + 4x = 15x 33 + 15x = -12 + -4x + 4x Combine like terms: -4x + 4x = 0 33 + 15x = -12 + 0 33 + 15x = -12 Add '-33' to each side of the equation. 33 + -33 + 15x = -12 + -33 Combine like terms: 33 + -33 = 0 0 + 15x = -12 + -33 15x = -12 + -33 Combine like terms: -12 + -33 = -45 15x = -45 Divide each side by '15'. x = -3 Simplifying x = -3
| -6-3=3-6y | | 2x+3=10+x | | -r+(3r^2+1)r=4 | | 5x-12x-7=8 | | -8=f/5 | | 38-4x=6(x+8) | | -3=k+3 | | (2t^2+7t-6)-(3t^2-11t-9)=0 | | 23=3+37t-16t^2 | | -8=2+3m-1 | | 5(x+3)-(2x-1)=3 | | 0.35x+.05(12-x)=.10(-48) | | -8=2+9m-1 | | 4x-9x=39 | | d-4.9=18.8 | | -[7x-(3x+10)]=-3-[4(2x-4)-2x] | | 3(3n+3)=9(6n+5)8 | | 6(x-5)=-48 | | 0.5x-0.3(2-x)=4.6 | | -4=a+6 | | 9x^2+3x-3xy-y=0 | | 5x^2-2x^2+9x^2+x^2=0 | | .01x+.10x+.25(35-2x)=4.07 | | 5+3x+2x+7=2 | | 4p^3+36p=0 | | 42-x=19 | | c-4=13.7 | | 6x*x+7x-20=0 | | n-6=-10 | | 0=x^2-25x+144 | | 9(5+x)=15(10+x) | | 4x-(9-3x)=18x-1 |